Transmission of Clostridium difficile from asymptomatically colonized or infected long-term care facility residents. (31st May 2018) - Donskey, Curtis J.; Sunkesula, Venkata C. K.; Stone, Nimalie D.; Gould, Carolyn V.; McDonald, L. Clifford; Samore, Matthew; Mayer, JeanMarie; Pacheco, Susan M.; Jencson, Annette L.; Sambol, Susan P.; Petrella, Laurica A.; Gulvik, Christopher A.; et al.
Abstract: Objective: To test the hypothesis that long-term care facility (LTCF) residents with Clostridium difficile infection (CDI) or asymptomatic carriage of toxigenic strains are an important source of transmission in the LTCF and in the hospital during acute-care admissions. Design: A 6-month cohort study with identification of transmission events was conducted based on tracking of patient movement combined with restriction endonuclease analysis (REA) and whole-genome sequencing (WGS). Setting: Veterans Affairs hospital and affiliated LTCF. Participants: The study included 29 LTCF residents identified as asymptomatic carriers of toxigenic C. difficile based on every other week perirectal screening and 37 healthcare facility-associated CDI cases (ie, diagnosis >3 days after admission or within 4 weeks of discharge to the community), including 26 hospital-associated and 11 LTCF-associated cases. Results: Of the 37 CDI cases, 7 (18·9%) were linked to LTCF residents with LTCF-associated CDI or asymptomatic carriage, including 3 of 26 hospital-associated CDI cases (11·5%) and 4 of 11 LTCF-associated cases (36·4%). Of the 7 transmissions linked to LTCF residents, 5 (71·4%) were linked to asymptomatic carriers versus 2 (28·6%) to CDI cases, and all involved transmission of epidemic BI/NAP1/027 strains. No incident hospital-associated CDI cases were linked to other hospital-associated CDI cases. Conclusions: Our findings suggest that LTCF residents with asymptomatic carriage of C. difficile or CDI contribute to transmission both in the LTCF and in the affiliated hospital during acute-care admissions. Greater emphasis on infection control measures and antimicrobial stewardship in LTCFs is needed, and these efforts should focus on LTCF residents during hospital admissions.